Prevalence of gingivitis and perception of gingival colour among pregnant women attending the antenatal clinic of Lagos University Teaching Hospital, Idi-Araba - Modupeoluwa Omotunde Soroye; Partricia Omowunmi Ayanbadejo (Wolters Kluwer Medknow Publications, 2016)
Objective: To determine the prevalence of gingivitis and perception of gingival colour among pregnant women attending the antenatal clinic of a tertiary health institution in Lagos State, Nigeria. Materials and Methods: A single-point assessment was conducted using a self-reported questionnaire completed by participants. Information such as patients' age, gestational age, educational status, occupation, and perception of gingival colours was obtained. Furthermore, the participants were examined by trained dentists to determine their gingival colours and the presence and severity of gingival inflammation. The data obtained were processed, and descriptive and comparative analyses were done using Epi info version 3.5.1 (2008). Statistical significance was established at P values <0.05. Results: Four hundred and forty-five pregnant women aged between 18 years and 43 years [mean age: 30.3 (±4.61) years] participated in the study. Gestational age was between 4 weeks and 41 weeks with a mean of 23.49 (±9.53) weeks. The prevalence of gingivitis was 85.2%. Two hundred and thirty (51.7%) participants described their gingival colour as pink, 127 (28.5%) as red, 51 (11.5%) as black, 3 (0.7%) as white, 2 (0.4%) as brown, and 32 (7.2%) could not determine the colour of their gingivae. Two hundred and ten (47.2%) participants knew that pink was the normal colour of a healthy gingiva. From objective clinical examinations by dentists, 344 (77.3%) patients had pink gingivae, 85 (19.1%) had pigmented gingivae, and only 16 (3.6%) had red gingivae. Conclusion: The higher prevalence of gingivitis during pregnancy is well-established and that observation is corroborated by this study. Since a change in gingival colour may be an early indication of gingival inflammation, early detection and prompt treatment could prevent further periodontal deterioration. Hence, there is the need to incorporate and intensify oral health education during antenatal care so that pregnant women are able to identify changes in gingiva colour, especially when it is associated with periodontal inflammatory diseases.